2004
DOI: 10.1007/s10227-005-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Psoriasis Therapies: An Update and Introduction to Biologic Therapy

Abstract: Biologic agents offer new hope for patients with psoriasis that their chronic condition can be controlled in a manner that improves their quality of life and may lead to high levels of satisfaction with their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Overall, the majority of respondents were very satisfied with biologics. This is consistent with previous studies that had reported high satisfaction rates amongst patients using biologic therapies(10, 11). Thus, physicians should not hesitate to tell patients who are considering starting biologics that despite the risks of adverse effects or not responding to these medications, the great majority of patients on biologics are satisfied with their treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the majority of respondents were very satisfied with biologics. This is consistent with previous studies that had reported high satisfaction rates amongst patients using biologic therapies(10, 11). Thus, physicians should not hesitate to tell patients who are considering starting biologics that despite the risks of adverse effects or not responding to these medications, the great majority of patients on biologics are satisfied with their treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Inadequate responses reported by patients as no change or even worsening of disease with treatment from 10% to 50%. Usually, nonbiologic therapies have a very high degree of dissatisfaction from the patients (Nijsten et al 2005;Finlay and Ortonne 2004) and the inconvenience and safety of traditional therapies become an issue for the patients. On the other hand, cyclosporine, methotrexate, and acitretin were qualified as highly effective in another survey (Strober et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Development of new biologics is favored because traditional topical therapies, phototherapy, and systemic medications have been associated with patient frustration10 and low compliance 11,12. Furthermore, topical treatments and phototherapy do not improve joint damage that is ongoing in psoriatic arthritis, and traditional systemic agents can cause long-term organ damage, such as pulmonary fibrosis and cirrhosis in patients on methotrexate.…”
Section: Introductionmentioning
confidence: 99%